MAJOR PROJECT MANAGEMENT FACTORS AFFECTING THE DELIVERY OF GREEN BUILDING PROJECTS: THE CASE OF JORDAN - Mukattash, Mais; Hyarat, Esraa (Journal of Applied Engineering Science, 2022)
Construction projects have significant impacts on the environment. They adversely affect many areas, such as energy consumption, global warming and resource depletion. Green buildings have been found to be the most effective way to reduce these impacts. As a developing country with limited resources, Jordan is giving too much prominence to sustainability in construction projects. However, moving forward with Green Building Projects (GBPs) is a great challenge. Most managers do not have much experience in managing these projects yet. They are not fully aware of the importance of project management factors which can significantly affect the delivery process of GBPs. Research addressing these factors has become a crucial need in the construction industry. The main objective of this study is to identify the major project management factors required to deliver GBPs successfully in Jordan. The questionnaire was distributed to determine the significance of nineteen project management factors and SPSS software was utilized to perform the data analysis. The results show that for GBPs in Jordan to be successfully delivered, there must be clear lines of communication during the design and planning stages. The study concludes with recommendations for improving GBP distribution in Jordan. A further detailed study is needed to investigate and improve communication channels in GBPs. The practical implications of this study are to help the stakeholders in the construction industry understand management activities in the green building industry in a better and more realistic way. In addition, identifying these factors will help control future projects and ensure correct decisions are made from the beginning of the project to maximize the project’s success.